STUDI POPULASI NYAMUK DEMAM BERDARAH DENGUE (DBD) DI KELURAHAN WIDODOMERTANI, YOGYAKARTA - Hurip Pratomo; Edi Rusdiyanto (Jurnal Matematika Sains dan Teknologi, 2003)
AnticipatingDHF outbreak possibility in Kelurahan Widodomertani -Kabupaten Sleman Yogyakarta was necessary done a research. Theresearch covered a study about vector DHF (Dengue HaemorhagicFever) population in Kelurahan Widodomertani. Main activitiesstudying a relative population were larvae and adultmosquitoes surveilance. Those surveilance did to achievelarvae index i.e.: HI (House Index), CI (Container Index), BI(Breteu Index), and the mosquitoes index was HDI (HouseDensity Index). Meanwhile mosquitoes identification need to bedone as well. The research was carried out in March 2002 andSeptember 2002. The results described the small possibilityhaving an outbreak of DHF in a short time. There were foundthree species of mosquitoes i.e.: Aedes albopictus, Culexquinquefasciatus, and Anopheles aconitus. Index values oflarvae and adult mosquitos were HI= 20.0%, CI= 17.6%, BI=16.0%, and HDI= 0.30 in March 2002, increased to HI= 36.7%,CI= 30.8%, BI= 26.0%, and HDI= 0.56 in September 2002.